ANTHROPOGENIC Zn CONTAMINATION DISPERSION IN SEPETIBA BAY EVIDENCED BY Zn ISOTOPES - Cunha, Bruno; Araújo, Daniel; Garnier, Jeremie; Dantas, Elton; Babinski, Marly; Ruiz, Izabel; Souto-Oliveira, Carlos Eduardo; Geraldes, Mauro; Rocha, Davi; Machado, Wilson (Geochimica Brasiliensis, 2022)
Sedimentary processes in coastal environments play a key role in the spatial dispersion of metal contaminants, including Zn. Combining Zn stable isotope signatures (δ66Zn) with traditional proxies of sedimentary sources and dispersal and post-depositional processes is a promising approach to understanding Zn anthropogenic dynamics in coastal systems that remains untested. To this end, we coupled geochemical and isotope tools to infer sedimentary contributions on Zn fate and behavior in surface sediments of Sepetiba bay, a tropical lagoon in Rio de Janeiro state chronically contaminated by an old stake of electroplating wastes Zn-enrich. Our results show high variability in δ66Zn values (0.43‰ to 0.89‰) and Zn enrichment factors (1 to 23-fold), evidencing a gradient in mixing sedimentary sources. The biplot δ66Zn versus 1/[Zn] highlights that the Zn isotope variability of most samples fell within a mixing source trend involving natural Zn (+0.29‰, 67 mg.kg-1) and anthropogenic Zn (+0.89‰, 3,440 mg.kg-1), the latter attributed to the Sepetiba bay’s historical Zn metallurgical contamination. Based on the isotope mixing model and geochemical proxies (e.g., Ti/Al ratio), we calculated that Zn excess in the Sepetiba Bay varies from 42% to 98%. The Zn enrichment distribution across the bay confirmed anthropogenic Zn dispersal from the Saco de Engenho, mainly controlled by the clock direction water current. Sediments mineralogical composition and correlations between Zn isotope and Al concentrations indicate that the high content of anthropogenic Zn is associated with silt and clay sediment particles composed of gibbsite and clay minerals such as kaolinite and organic matter. Our findings demonstrate that combining Zn isotope ratios with other geochemical proxies may help pinpoint Zn anthropogenic origins and behavior as well as track its dispersion in the land-sea continuum. In this case, this approach provides more accurate results on Zn contamination dispersion in the Sepetiba Bay and avoids possible misleading interpretations concerning anthropogenic Zn origins at low Zn concentration levels.